Childhood-onset lupus with clinical neurocognitive dysfunction shows lower streamline density and pairwise connectivity on diffusion tensor imaging. (September 2015) - Jones, J T; DiFrancesco, M; Zaal, A I; Klein-Gitelman, M S; Gitelman, D; Ying, J; Brunner, H I
Objectives: The objective of this report is to use diffusion-tensor imaging (DTI) for investigating white-matter connectivity changes associated with neurocognitive dysfunction in childhood-onset lupus (cSLE-NCD) as measured by formal neuropsychological testing. Methods: DTI was performed in six individuals with (cSLE-NCD) and nine without neurocognitive dysfunction (cSLE-noNCD) as well as 14 healthy controls. Presence of neurocognitive deficits was identified by formal neuropsychological testing. The brain was divided into 116 regions, and pairwise connectivity (defined as the number of streamlines with an endpoint in each of those regions) and streamline density (defined as the number of streamlines passing through a region regardless of endpoints) were evaluated. Group comparisons were made for regional and global measures of streamline density and pairwise connectivity. Results: A significant decrease in global streamline density was observed in the cSLE-NCD vs. control group (1189 vs. 1305 p = 0.002) and vs. cSLE-noNCD (1189 vs 1320 p = 0.001). The cSLE-noNCD and control groups had similar streamline density. A similar pattern for pairwise connectivity was observed with a significant decrease in the cSLE-NCD group (217) versus the cSLE-noNCD (236; p = 0.013) and control group (238; p = 0.004). Regional measures of pairwise connectivity displayed mixed results. Conclusions: The analysis of DTI in this pilot study shows cSLE-NCD is associated with global loss of streamline density and pairwise connectivity, suggesting breakdown of the structural network. These results complement previously reported functional and volumetric findings that suggest cSLE-NCD is associated with measurable changes in gray and white matter. If confirmed in larger cohorts, DTI abnormalities could be used as imaging biomarkers of cSLE-NCD.